THE USE OF ROBOTS TO AUTOMATE HAZARDOUS AND LABOR-DEMAND MANUFACTURING PROCESSES (Academia Science Repository, 2023)
Automation of production processes using robots has many advantages, especially in hazardous and labor-consuming processes that allow to improve worker working conditions, improve product quality and reduce production costs. However, when using robotics, it is necessary to take into account the social, economic and moral aspects of this process, as well as to provide opportunities for learning new skills and rehabilitating workers. Only if all of these conditions are met can it be guaranteed to improve the working conditions of the employees and increase the efficiency of production.